Non-verbal clauses with demonstrative identifiers in the history of Croatian - Šimić, Ana, lingvistkinja (Array, 2019)
The paper presents a corpus-based typological and diachronic study of nonverbal clauses with demonstrative identifiers in Croatian. As one of the four types of demonstratives proposed by H. Diessel, demonstrative identifiers occur in copular and non-verbal clauses. They are used to focus the hearer’s attention on entities in the surrounding situation or in the universe of discourse. The paper reviews the typologies of demonstratives discussed in recent literature with respect to the status of demonstrative identifiers. Furthermore, it investigates the history of non-verbal clauses with demonstrative identifiers in Croatian: 1. se človêkь 2. evo čovjeka DEM man-NOM.SG DEM man-GEN.SG ‘Here is the man!’ ‘Here is the man!’ The main change occurred in the case marking on the argument. In the first Croatian literary language, Croatian Church Slavonic (1), the argument appears in the nominative case. In contemporary Croatian (2), the demonstrative identifier is predominantly followed by a genitive argument. Apart from shedding some light on the diachronic development of non-verbal clauses with demonstrative identifiers and their constituents in Croatian, the paper shows how they differ from similar constructions in other Slavic languages, as well as in some major European languages. In addition, they are compared to other non-verbal constructions with genitive and nominative arguments in Croatian.